Three-dimensional topography modelling of regular prismatic grain coated abrasive discs - Arunachalam, Adhithya Plato Sidharth (2020)
Regular precision-shaped abrasive grains are preferred to irregular grits due to their superior performance regarding uniform polishing. Three-dimensional modelling of abrasive disc’s topography is essential to understand the material removal rate and surface roughness estimations through finite element based numerical simulations. Topography modelling of one such precision (prism)-shaped grain abrasive disc is carried out in this work through stochastic studies. The abrasive discs are scanned using laser profilometer, and high-frequency noise is filtered out using spectral analysis. Spatial parameters such as autocorrelation length and texture aspect ratio are considered for the topology mapping. Based on the statistical information from the measured grit sizes #60 and #120, such as peak protrusion grain height, spatial distributions, the topography is simulated. The analysis reveals that the peak height and spatial distribution follow a normal distribution. Unlike irregularly shaped grains where the orientations of the grains are neglected, the height variations in the precision-shaped grains in coated abrasive discs are mainly caused by random orientations of the grains. So, iterations are carried out for orientation in the three (mutually perpendicular) axes of the grain till the required statistical parameters are achieved. Surface fitting is performed for the distributed grains and the 3D-surface parameters of the simulated coated abrasive topography match well with the actual discs.